Comparação entre duas subespécies de oxyrhopus melanogenys (tschudi, 1845) com descrição de hemipênis (serpentes: colubridae: xenodontinae: pseudoboini) - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1997)
The South American false coral snake Oxyrhopus melanogenys (Tschudi, 1845) is surrounded by a great systematic complication. Considering only the chromatic pattern and the presence of "intergrading" individuals, the species was divided into two subspecies, an oriental, Oxyrhopus m. orientalis Cunha & Nascimento, 1983; and the nominal, western. In order to verify the validity of the oriental taxon, a comparative study of the two subspecies was carried out considering traditional features such as scale count (lepidose) and coloration patterns, and other new features for the taxa, such as cephalic shield morphometry and analysis of internal structures like hemipennis (male genitalia) and cephalic myology. We used 17 specimens of O. m. melanogenys and 97 of O. m. orientalis (including all type-series), deposited in the Herpetological Collection of the Museu Paraense Emílio Goeldi (MPEG). The recharacterization of O. m. orientalis, represented by specimens with a coloration pattern consisting of red background color with two black bands in the nuchal region and triads distributed throughout the body, moderate length, with the largest equal to l 076 mm (N=83 measured), ventral scales 186-210 (N=94), subcaudal scales 69-93 (N=80), supralabial shields usually 8/8 (N=92), 8/9 (Ne l), 9/9 (N= 1), with the 4th and 5th in contact with the ocular orbit, infralabial shields 10/10(88.04%, N=92), bilobed, spiny hemipennis, typical of Pseudoboini, similar to that of O. m. melanogenys, which has meristic characters with the same range of variation, but with a distinct coloration pattern from O. m. orientalis, consisting of a reddish background color and two black bands in the nuchal region. The absence of the probable intergraders, cited in the literature, in the area of possible intergradation, suggests the specific status for O. m. orientalis.
Comparison of two subspecies of oxyrhopus melanogenys (tschudi, 1845) with description of hemipennis (snakes: colubridae: xenodontinae: pseudoboini)
Keywords: Oxyrhopus melanogenys; Oxyrhopus m. orientalis; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA